Development of an Internet of Things system for lubrication oil level monitoring - Mat Hussain, Nur Shaebah; Mohd Ariffin, Mohd Khairol Anuar; Ahmad, Siti Azfanizam; Mohamed, Zulkifli (UiTM Press, Universiti Teknologi MARA, 2025)
Lubricant demand is predicted to keep growing in global markets. As a result, the lubrication industry should periodically measure the quantity of lubricant stock to guarantee its safety. Both software and hardware make up the constructed lab model of the Internet of Things system. Among the specialized parts of the system are a LiDAR sensor, an Arduino Esp32 microcontroller, and a network architecture. The sensor, which is mounted on top of the tank, collects data, which is subsequently transmitted to the microcontroller for processing. The sensor's primary function is to determine the level of lubricant in the tank. The data processing and link establishment for the network infrastructure are both handled by the microcontroller. Blynk Apps, a communication platform, is integral to the development of the system that is being created. In the event of an emergency, the system may either be automated or manually operated. The software has been programmed in such a way that it is able to send commands to the sensor using Blynk Apps from any place, provided that both connections are stable. The system provides the benefits of having a low cost as well as portability. The system is able to offer reliable data on the amount of the lubricant, which makes it possible to do maintenance and restock at appropriate time.